Effects of reinforcement corrosion on the structural performance of reinforced concrete beams - Theron, Gavin De Vos (Department of Civil Engineering, 2016)
This dissertation is an investigation into the effect of reinforcement corrosion on the structural performance of reinforced concrete beams. Two types of specimens are investigated, the first without any stirrups and the second with stirrups. The specimens were corroded galvanostatically as well as by subjecting them to alternate cycles of wetting and drying with a saline water. An attempt is made at classifying the extent of corrosion of the reinforcing steel and its effects on the concrete. The effect of the corrosion on the structural performance is measured by establishing its effect on the maximum load carrying capacity, the deflections, energy requirements and ductility ratio. The main conclusions made in respect of the effect of reinforcement corrosion are that it causes: a decrease in the load carrying capacity; an increase in the deflections at the equivalent load level; a decrease in the energy requirements to reach the maximum load; and a smoothing of the load-deflection relationship. A limited literature review is also presented to provide background information of corrosion in concrete and general structural behaviour. Guidelines for the development of an analytical model to predict the load carrying capacity of corrosion affected reinforced concrete beams are also given.